Conjugative transfer of multi-drug resistance IncN plasmids from environmental waterborne bacteria to Escherichia coli - Guzman-Otazo, Jessica; Joffré, Enrique; Agramont, Jorge; Mamani, Nataniel; Jutkina, Jekaterina; Boulund, Fredrik; Hu, Yue O. O.; Jumilla-Lorenz, Daphne; Farewell, Anne; Larsson, D. G. Joakim; Flach, Carl-Fredrik; Iñiguez, Volga; et al. (Frontiers in Microbiology, 2022)
Watersheds contaminated with municipal, hospital, and agricultural residues are recognized as reservoirs for bacteria carrying antibiotic resistance genes (ARGs). The objective of this study was to determine the potential of environmental bacterial communities from the highly contaminated La Paz River basin in Bolivia to transfer ARGs to an Escherichia coli lab strain used as the recipient. Additionally, we tested ZnSO4 and CuSO4 at sub-inhibitory concentrations as stressors and analyzed transfer frequencies (TFs), diversity, richness, and acquired resistance profiles. The bacterial communities were collected from surface water in an urban site close to a hospital and near an agricultural area. High transfer potentials of a large set of resistance factors to E. coli were observed at both sites. Whole-genome sequencing revealed that putative plasmids belonging to the incompatibility group N (IncN, IncN2, and IncN3) were predominant among the transconjugants. All IncN variants were verified to be mobile by a second conjugation step. The plasmid backbones were similar to other IncN plasmids isolated worldwide and carried a wide range of ARGs extensively corroborated by phenotypic resistance patterns. Interestingly, all transconjugants also acquired the class 1 integron intl1, which is commonly known as a proxy for anthropogenic pollution. The addition of ZnSO4 and CuSO4 at sub-inhibitory concentrations did not affect the transfer rate. Metal resistance genes were absent from most transconjugants, suggesting a minor role, if any, of metals in the spread of multidrug-resistant plasmids at the investigated sites.